Implementation of Operational Risk Management to Mitigate Employee Fraud in Banking Companies: Case Study at PT AAA - Hanggraeni, Dewi; Andintyas, Muhammad Chandika (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 1 Tahun 2021DO - 10.24843/MATRIK:JMBK.2021.v15.i01.p13, 2021)
This study aims to describe the potential losses due to employee internal Fraud using a case study at PT AAA in 2020 and its mitigation. The data used is the monthly loss data experienced by PT AAA for the period 2012 to 2019. The research methods used are quantitative and qualitative approaches. The quantitative method is applied by analyzing the calculation of the primary data, while the qualitative method is carried out by conducting interviews with several sources. To measure potential losses, this study uses the Monte Carlo formula and to process of calculating potential losses is assisted by Easyfit software. The results of this study indicate that the potential loss arising from operational risk due to Fraud by internal employees with a 95% confidence level is IDR 44,880,958,735,- or 9% of Net Income. This study also formulates a risk register so that it can be used as a reference for mitigating related risks to reduce potential losses and increase shareholder value.